Managerial accounting - Raiborn, Cecily A.; Barfield, Jesse T.; Kinney, Michael R. (Cincinnati ; London : South-Western College, 1999)
This book is divided into five parts: The business environment; The basics of managerial accounting; Using managerial accounting information for planning; Using managerial accounting information for product costing; and Using managerial accounting information for control.
Keywords: Accounting; Managerial accounting